Inovasi Pembuatan Pupuk Berbasis Limbah Kayu dan Manajemen Usaha di Kelurahan Oesapa: Innovation in Making Fertilizer Based on Wood Waste and Business Management in the Oesapa Village - Christian Daniel Manu; Angela Merici Minggu; Yuningsih Nita Christiani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The trend of healthy living has become a choice for the wider community. One way to support a healthy life is by planting various plants, which are a source of natural vitamins and herbal medicines. Communities in the Kupang City area are also moved to follow the growing trend of healthy living, namely, back to nature. In supporting the community's activities of growing plants for daily consumption and sources of herbal medicines, the effort that can be taken is to provide natural fertilizers that can be obtained quickly and cheaply by the community. Therefore, this community service activity responds to the phenomenon by teaching the manufacture of organic fertilizer from wood waste. This activity can be a business option for the community to create a new source of income. The community is also equipped with knowledge about business management so that they can run new types of businesses. The method used in this PKM activity is to conduct initial discussions with people who are willing to produce organic fertilizer from wood waste, conduct surveys of furniture business locations in the Kupang City area to obtain wood sawdust raw materials, carry out the organic fertilizer production process, mentoring product packaging, product labeling, and marketing, as well as explaining simple business management processes that the community can apply. The output of this PKM is wood waste organic fertilizer products, product labeling, and a simple business management model.